Deroofing followed by thorough sinus tract excision: a modified surgical approach for hidradenitis suppurativa - Dahmen, Robert Artur; Gkalpakiotis, Spyridon; Mardesicova, Libuse; Arenberger, Petr; Arenbergerova, Monika (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
BACKGROUND AND OBJECTIVES: Deroofing has proven to be an effective method to treat mild to moderate forms of hidradenitis suppurativa (HS). The basic procedure includes removal of the sinus roof, followed by secondary intention healing, while fibrotic tissue usually stays in situ. We have tried to establish a modified method of deroofing in which meticulous removal of the fibrotic tissue results in a low recurrence rate in moderate to severe HS patients. PATIENTS AND METHODS: An open prospective study consisted of 96 deroofed lesions in 52 consecutive patients with moderate to severe HS. Patients were followed up for a minimum of 28 months. RESULTS: Recurrence occurred after a median time of 2.3 months in 14 % of locations. Recurrences according to location were as follows: 6 % in the axillary region and 25 % in the inguinal region. Postoperative bleeding was the only considerable complication and occurred in 7 % of treated locations. Seven patients were lost to follow-up. CONCLUSION: Modified deroofing followed by meticulous sinus tract removal is a surgical approach suitable for patients with moderate disease, especially in the axillary region. This results in a low recurrence rate and the same healing period as that of the standard deroofing procedure.
Keywords: dospělí; Recurrence; Female; Adult; Hidradenitis Suppurativa; ženské pohlaví; Lost to Follow-Up; Wound Healing; chirurgie operační; axila; lidé; recidiva; pooperační komplikace; Postoperative Hemorrhage; subjekt ztracen ze sledování; stupeň závažnosti nemoci; Inguinal Canal; debridement; prospektivní studie; pooperační krvácení; Male; Postoperative Complications; Prospective Studies; Axilla; Debridement; Czech Republic; Visual Analog Scale; hojení ran; Česká republika; mužské pohlaví; inguinální kanál; Severity of Illness Index; Surgical Procedures, Operative; vizuální analogová stupnice; hidradenitis suppurativa; Humans